Time‐domain homogenization of multiturn windings based on RL Cauer ladder networks. (14th August 2019) - Niyomsatian, Korawich; Gyselinck, Johan; Sabariego, Ruth V.
Abstract: This paper deals with the synthesis of an RL Cauer ladder network to homogenize multiturn windings in time‐domain finite element (FE) computations. In frequency domain, the macroscopic model of eddy currents in the winding can be described by frequency‐dependent complex impedance and reluctivity for skin and proximity effects respectively. To represent those in time domain, two RL Cauer networks are synthesized to match each, with the accuracy depending on the order of the network to be appended. The proposed method yields an improved accuracy as compared with the previous work in which the topology of the ladder network was not well chosen. The results are validated by means of a 2‐D axisymmetric inductor with a nonlinear gapped core.